Biosorption Of Copper(II) And Chromium(VI) Onto Activated Sludge : Isotherms And Kinetic Models - Chan, Poh Ying (2007)
The objectives of this research are: (i) to evaluate the efficiency of laboratoryprepared sludge for the removal of Cu(ll) and Cr(VI) individually and in combination from aqueous solutions, (ii) to ascertain appropriate adsorption equilibrium models for both single and binary metal systems using the laboratory-prepared sludge and (iii) to ascertain appropriate adsorption kinetic models for the single metal system using the laboratory-prepared sludge. The sludge used in this study was cultivated in three identical laboratory-scale sequencing batch reactors (SBR) operated with FILL, REACT, SETTLE, DRAW and IDLE periods in a ratio of 2: 12: 2.5: 1.5: 6 for a cycle time of 24 h. Sludges of 20-, 30- and 40-day sludge ages were prepared by wasting a fixed amount of mixed liquor from the respective reactor just before the end of the REACT period during every cycle.